Progress with the delivery of Intermediary Performance Indicator IPI 1.3 of AICCRA-AF: New soil mapping generated by the West african Regional Hub for Fertilizer and Soil Health - Kadja, Lionel Axel; Vanlauwe, Bernard; Mkuhlani, Siyabusa; Shehu, Bello; Sinha, Surajit; Sehou, Romaric; Dalaa, Mustapha Alasan; Ampadu Boakye, Theresa (2025)
Scoping missions in 11 West African and Sahelian countries to assess demand for technical assistance on fertilizer and soil health. Seven countries were selected Nigeria, Ghana, Togo, Liberia, Sierra Leone, Mali, and Senegal based on expressed demand, institutional readiness, and the presence of active scaling programs. The Intermediary Performance Indicator (IPI) 1.3 responds to governments and Soil Values programme requests for Digital Soil Mapping (DSM) in priority agricultural watersheds, with the aim of supporting the generation of locally relevant ISFM recommendations. Target areas cover 2.9 million ha in Nigeria and 1.3 million ha in Mali. Progress to date includes the completion of V0 maps using ISRIC SoilGrids data sets and V1 maps integrating legacy datasets from IFDC, iSDA, OCP Africa, and Soils4Africa. V2 maps, based on new soil sampling, will be delivered by Mid November and during the first quarter of 2026. Two complementary workstreams are underway: the development of national Soil Information Systems (SIS) to host and update soil and agronomic data, and the establishment of a regional hub-and-spoke model for analytical laboratories to improve soil and plant testing capacity. In partnership with ECOWAS, the Hub will also develop a dynamic soil health and fertilizer dashboard and expand its regional knowledge repository. Future work under AICCRA-III will shift from DSM generation toward fully operational SIS platforms, strengthened laboratory networks, and long-term decision-support services at national scale.